A adaptação da educação infantil montessoriana em um contexto de ensino remoto: um estudo de caso - Tonial, Celine Natali Daronchi (2022)
This research concerns the analysis of educational processes in Preschool Education from the concept of Montessori theory and the way they were developed during the Covid-19 pandemic from an Online Education perspective. Thus, it becomes the objective of the investigation to analyze a process of adaptation of Montessori Preschool Education to remote teaching during the Covid-19 pandemic. In order to achieve this purpose, a bibliographical study was carried out, based on theoretical references that discuss Preschool Education and Online Education, based on the researches of Lévy (2010 and 2011), Montessori (1987, 2017, 2018 and 2019), Papert (1994) and Silva (2012 and 2014). From this theoretical contribution, the methodological procedures were established in qualitative research, with a descriptive exploratory case study approach, involving interviews and questionnaires, as well as the analysis of the participating school's blog. The case study will be developed in a private school in Passo Fundo/RS, in 2022. For a better understanding of the educational processes that took place during the Covid-19 pandemic, the following were selected for the research: the direction, pedagogical coordination, teachers and families of children from Kindergarten, in search of analysis of actions and activities during this period. It was observed that, in fact, there were implications of Online Education in Early Childhood Education, which resulted in educational potential and challenges in the post-pandemic period. From the answers obtained in the interviews and the analysis of the potential of the use of the blog, we realized that there were important growths in the subjects involved in the pedagogical processes in the pandemic. Finally, it is emphasized that Online Education can be powerful and qualified, if it is carried out with study, planning, intentionality and with the use of digital pedagogical resources designed for each age group, in addition to the students' understanding of using it as an agent. of learning. The study brings relevant results to the implications of remote teaching in Early Childhood Education, especially with regard to the learning and socialization of children during the pandemic period, in addition to the strategies created by the school to enhance and qualify access and communication between the entire school community. Thus, it is highlighted that Online Education, when developed with study, planning, intentionality and with the use of digital pedagogical resources designed for each age group, builds significant and qualified pedagogical proposals for the teaching and learning of children.